Effect of Addition of SBS Polymer and Zycotherm on Bitumen and Bituminous Concrete Mix Prepared With Riverbed & Limestone Aggregate - Singh, Harpreet (My University, 2017)
In this study, the bitumen was doped with various percentages of SBS polymer and Zycotherm additive. Comparison was made between Base bitumen, SBS modified bitumen and Zycotherm modified bitumen. The dosages of SBS polymer were taken as 3, 5 and 7%, which were added to the optimum binder content and the Marshall Stability and the flow of the mixes were determined. Zycotherm additive dosage was kept 0.1% for all mixes. The effects of SBS content and Zycotherm additive on bitumen were examined by using Marshall Stability, Indirect Tensile Strength (ITS) test and rheological test. Marshall Stability of the SBS modified bitumen at 5% dosage of SBS polymer was found to be optimum as compared to 3% and 7% polymer content. The Indirect Tensile Strength of SBS modified bitumen was higher at 5% SBS content as compared to 3% and 7%. Zycotherm additive has not shown any significant effect on properties of mix. It observed that best results were obtained by using 5% of SBS polymer and Zycotherm additive has no effect on mechanical properties of mix. Rheological test on different binders has shown that Zycotherm additive has very less affect on rutting resistance of modified bitumen. 5% SBS modification in bitumen showed better performance in rutting resistance potential of bituminous mixes. However the viscosity of SBS modified bitumen is higher which will require more mixing temperature to properly coat the aggregate with binder, so Zycotherm additive can be used which will reduce the viscosity of SBS binder at high temperature. Addition of Zycotherm will result in lower mixing and compaction temperature without compromising the performance of bituminous mix.
Master of Engineering -Civil Infrastructures
Keywords: SBS; ZYCOTHERM; dynamic shear rheometer